Impact of decompressive laminectomy on the functional outcome of patients with metastatic spinal cord compression and neurological impairment - Younsi, Alexander; Riemann, Lennart; Scherer, Moritz; Unterberg, Andreas; Zweckberger, Klaus (Clinical & experimental metastasis, 2020)
Metastatic spinal cord compression (MSCC) is a frequent phenomenon in advanced tumor diseases with often severe neurological impairments. Affected patients are often treated by decompressive laminectomy. To assess the impact of this procedure on Karnofsky Performance Index (KPI) and Frankel Grade (FG) at discharge, a single center retrospective cohort study of neurologically impaired MSCC-patients treated with decompressive laminectomy between 2004 and 2014 was performed. 101 patients (27 female/74 male; age 66.1 ± 11.5 years) were identified. Prostate was the most common primary tumor site (40%) and progressive disease was present in 74%. At admission, 80% of patients were non-ambulatory (FG A-C). Imaging revealed prevalently thoracic MSCC (78%). Emergency surgery (< 24 h) was performed in 71% and rates of complications and revision surgery were 6% and 4%, respectively. At discharge, FG had improved in 61% of cases, and 51% of patients had regained ambulation. Univariate predictors for not regaining the ability to walk were bowl dysfunction (p = 0.0015), KPI < 50% (p = 0.048) and FG < C (p = 0.001) prior to surgery. In conclusion, decompressive laminectomy showed beneficial effects on the functional outcome at discharge. A good neurological status prior to surgery was key predictor for a good functional outcome.